Study on material properties effect for maximization of thermoelectric power generation. (August 2019) - Karami Rad, Meysam; Rezania, Alireza; Omid, Mahmoud; Rajabipour, Ali; Rosendahl, Lasse
Abstract: Thermoelectric generators (TEGs) have mostly been used in niche applications due to the low efficiency. This study aims to evaluate the effect of different material transport properties such as Seebeck coefficient, thermal conductivity, and electrical resistivity, on the system-level performance of the TEGs. A mathematical model was developed in MATLAB and verified by the experimental data to evaluate various thermoelectric (TE) materials with unit figure of merit (ZT = 1) and with a diverse combination of properties. The results shows increment in the power factor with a factor of 15, which corresponds an enhancement in the thermal conductivity by factor of 13.33 for fixed ZT, can increase the power output up to 45%. The results moreover shows, higher power factor has more impact on the power generation at lower fill factors (FFs) and smaller thermal resistance of the heat sink and heat source. Highlights: Simple model is developed to study effect of material properties on TEG performance. The model was verified with experimental data. Effect of PF is more significant than the ZT for maximum output power. Materials with higher PF enhance the module performance.